Septic acute kidney injury (SAKI) - Vinayak Patki (Wolters Kluwer Medknow Publications, 2018)
Acute kidney injury (AKI) is a common and potentially fatal complication of sepsis. Septic acute kidney injury (SAKI) remains an important challenge in critical care medicine. SAKI has a complex pathophysiology than previously anticipated. The pathophysiologic mechanisms of sepsis-induced AKI are different from non-septic AKI. Sepsis- induced systemic inflammation triggers protective mechanisms within the nephron, affecting tubular and glomerular functions. A varying degree of kidney impairment can be expected, from a small decrease in GFR to complete shutdown and permanent dysfunction, depending on the severity of the inflammatory response. It is likely that progression of septic AKI can be prevented by avoiding hypotension, fluid overload, and venous congestion. There is no specific therapy for septic AKI at present. Even though novel drugs and blood purification techniques for sepsis-induced AKI are being tested, supportive care to prevent further kidney insults is likely to allow kidney structure and function to more easily recover once the septic state has resolved.